41 Using Patient Centred Care to Redesign Integrated Discharge Services in Derby. (6th February 2020) - Youde, J; Rawlings, J; Knight, J
Abstract: Background: Discharge to Assess as outlined by the Department of Health was adopted in Derby in 2016. Previously the discharge pathways to community settings from the acute trust were complex. Challenges included: Operating from a traditional residential care home. No integration of community health staff and social care teams leading to delays in treatment and decision making as well as multiple referrals and hand-overs and no joint communication which was confusing for patients. Stakeholder anticipation of 6 weeks length of stay. Limited responsiveness to capacity demand within planned and unplanned community physiotherapy. Changing the culture and mind-set of staff. Different health and social care processes and procedures, IT systems, working patterns, contracts and pay scales. Methods: A new service model, joint processes and standard operating procedures was developed with the patient at the centre of the design. Trusted assessment and information sharing reduce multiple assessments and hand overs, ensuring a smoother and improved patient experience. Outcomes: Triage of patients from the Integrated Discharge Hub to the appropriate pathway, early discharge planning, board rounds and MDT's and timely assessments combined with an enablement ethos have increased the flow of patients through the service, decreased care package hours and increased capacity through reducing both length of stay and delayed transfers of care. The health and social care teams are now delivering fully integrated care and undertaking joint training. This has led to a reduction in treatment times from 20 days to 12 days, reductions in DTOC to average of 8 days per month and improved access to community based routine therapy from 85% of referrals being seen by 6 weeks 2017-18 to 99% in 2018-19. Conclusions: The integrated service delivers more for less resulting in significant savings in the healthcare and social care system while maintaining quality standards and outcomes.